Ultrasonic misdiagnosis of giant pediatric testicular yolk sac tumor: A case report and literature review - Wang, Zilong; Lu, Fuding; Song, Changze; Wang, Xinkun; Li, Naifa; Zhai, Jiawen; Jiang, Baohong; Yuan, Jianpeng; Yang, Zheng; Xuan, Xujun (Frontiers in Pediatrics, 2022)
Background: Yolk sac tumor is the most common malignant nonseminomatous germ-cell tumor in children characterized by elevated level of α-fetoprotein (AFP), accounting for 70%-80% of all cases. However, giant yolk sac tumors which involves the entire testicle may be misdiagnosed by color Doppler ultrasonography as orchitis. Therefore, we described a case of a 2-year-old pediatric patient with a giant testicular yolk sac tumor which was misdiagnosed by ultrasonography as orchitis, in order to evaluate the role of measuring AFP levels in the initial diagnosis to aid in the accuracy of the definitive diagnosis of testicular yolk sac tumor. Case presentation: A 2-year-old boy received outpatient visits for unintentional swelling of the right scrotum for 7 days. Physical examination showed a rubbery swelling of the right scrotum with rejective touch. Then, the patient underwent perineal color Doppler ultrasonography in outpatient visits. The result showed a right testicle size of 29mm×22mm×20mm with heterogeneous echogenicity and abundant blood ﬂow, supporting the initial diagnosis of orchitis. However, the initial surgeon was skeptical of the ultrasonography diagnosis. Thus, the patient was admitted to the department of andrology on Day 2 for further serological and imaging examination. The serum AFP level on Day 3 was 323.77ng/ml. The results of CT and MRI showed a giant tumor of the right testis (26mm×21mm×29.6mm) with multiple lymphoid hyperplasia in the inguinal region bilaterally. The patient received radical orchidectomy without lymph node dissection on Day 9. The results of postoperative pathological examination confirmed giant testicular yolk sac tumor (T1N0M0S1, Stage Is) and showed positive for AFP and SALL4 in immunohistochemistry staining. The patient received 3 courses of bleomycin-etoposide-cisplatin chemotherapy in the department of pediatrics after multidisciplinary team meeting on Postoperative Day 14, 37 and 58, respectively. During chemotherapy and follow-up, the patient's AFP and LDH levels continued to decline, eventually remained within normal range on Postoperative Day 84. Conclusion: Measuring AFP level was necessary for initial diagnosis and follow-up in a pediatric case of testicular enlargement. Radical orchidectomy combined with postoperative BEP adjuvant chemotherapy was an effective treatment strategy for pediatric giant testicular yolk sac tumors.